Stock photos of the Health Sciences campus in Boston and the Chinatown neighborhood. Photo 012 - Schutzengel, Aaron (Tufts Archival Research Center, 2008)
Stock photos of the Health Sciences campus in Boston and the Chinatown neighborhood.